2013
DOI: 10.1007/s11010-013-1612-z
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of atrial natriuretic peptide/natriuretic peptide receptor-A-mediated signaling upregulates angiotensin-II-induced collagen synthesis in adult cardiac fibroblasts

Abstract: Cardiac hormone atrial natriuretic peptide (ANP) and its receptor natriuretic peptide receptor-A (NPR-A) system acts as an intrinsic negative regulator of abnormal extracellular matrix (ECM) remodeling in the heart. However, the underlying mechanism by which ANP/NPR-A system opposes the ECM remodeling in the diseased heart is not well understood. Here, we investigated the anti-fibrotic mechanism of ANP/NPR-A in fibrotic agonist Angiotensin- II (ANG II)-treated adult cardiac fibroblast (CF) cells. Normal and NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…However, the exact mecha nism behind the regulators and the underlying mecha nisms controlling the expression and activation of these proteins in AFs are poorly understood. It has been shown that Ang II induces an increase in the synthesis of collagen I and collagen III in fibroblasts (27) and ERK induced collagen I and collagen III expression in cultured renal interstitial fibroblasts (28). In this study, we found that Ang II significantly induced the expression of collagen I and collagen III at both the protein and mRNA level and increased the expression of AP1 protein in AFs.…”
Section: Discussionsupporting
confidence: 58%
“…However, the exact mecha nism behind the regulators and the underlying mecha nisms controlling the expression and activation of these proteins in AFs are poorly understood. It has been shown that Ang II induces an increase in the synthesis of collagen I and collagen III in fibroblasts (27) and ERK induced collagen I and collagen III expression in cultured renal interstitial fibroblasts (28). In this study, we found that Ang II significantly induced the expression of collagen I and collagen III at both the protein and mRNA level and increased the expression of AP1 protein in AFs.…”
Section: Discussionsupporting
confidence: 58%
“…The network also shows NF-kB acting on up-regulated CCR2, a receptor involved in monocyte activation [50], on up-regulated CXCL1, the prototypical neutrophil chemokine [51], on up-regulated CXCL10, a leukocyte chemoattractant [52], and on up-regulated CCL19, a chemokine for dendritic cells and T lymphocytes [53]. NF-kB, activated by IL1R, the receptor for IL-1 [54], acts on up-regulated collagen I gene, a redundant effect mediated by C3a, C5a, and IL-1 [55]. C5a also acts on the fibronectin gene [56], and presumably its cognate protein, which can then activate up-regulated BMP1 and promote the formation of collagens I and III [57].…”
Section: Resultsmentioning
confidence: 99%
“…; Parthasarathy et al . ). The antifibrotic effects of NPs are also thought to involve alterations in activity or expression of matrix metalloproteinases and tissue inhibitors of metalloproteinases, proteins that play a critical role in the maintenance of the extracellular matrix (Kassiri & Khokha, ), in fibroblasts (Tsuruda et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Parthasarathy et al . ). It is presently unknown whether any of these effects specifically involve NPR‐C or whether expression of these proteins is altered in NPR‐C −/− mice.…”
Section: Discussionmentioning
confidence: 97%